Due Process of Law and the Principle of Al-'Adalah in the Selection of Constitutional Judges: A Critique of the Single Candidate Method - Anisa Anisa (Rechtsvinding, 2026)
The practice of selecting a single candidate for constitutional judges by Commission III of the House of Representatives (DPR) has emerged as a serious issue, as it violates the due process of law and contradicts the principle of al-’adalah in Islamic law. The closed nature of this process, which lacks public participation and is heavily influenced by transactional politics, threatens the independence of the Constitutional Court as the ultimate guardian of the rule of law. This study employs library research, utilizing data sources such as books, scientific journal articles, research reports, and official documents. The research reveals three primary findings. First, the single-candidate method breaches the principles of due process of law—particularly fairness, transparency, and the opportunity to be heard—and subsequently deprives other potential candidates of their constitutional rights. Second, this approach is inconsistent with the principle of al-’adalah, as it disregards both procedural and substantive justice, violates the 'adalah requirement for candidates, and dismisses al-musyawarah alongside the prohibition of al-muhasabah. Third, the convergence of these two principles provides a comprehensive critical framework and proposes an ideal selection model based on five pillars: an independent committee, open registration, a screening process, public examination, and final selection by the DPR. The study concludes that the single-candidate practice must be abolished, as it undermines the legitimacy of the recruitment process and the authority of the Constitutional Court. The practical implementation of these findings involves public advocacy, legislative revisions, and a fundamental shift in the political culture of the elite.